The pedagogy of death in Primary Education - Fornons Casol, Laura; Ramos-Pla, Anabel (Emerging Trends in Education, 2025)
The pedagogy of death proposes an integral education that incorporates death as an essential part of life, fostering emotional competencies, reducing anxiety about mortality, and offering a transformative approach that challenges taboos and curricular gaps in primary education. This study presents a theoretical review based on the models of Maureira et al. (2024) and Espinoza Freire (2020), employing hermeneutic, content, and analytical-synthetic analysis. Systematic reviews, bibliometric analyses, and relevant literature from databases such as WOS, Scopus, and Dialnet were examined, focusing on emotional impact, curricular integration, didactic strategies, and teacher training. Findings highlight that integrating the pedagogy of death into the educational system fosters skills such as resilience, self-regulation, and critical thinking while reducing anxiety related to mortality. However, significant gaps remain in teacher training and the absence of educational frameworks that normalize the topic within curricula. The study advocates for the transversal integration of this subject, designing innovative and interdisciplinary teaching strategies and assessing their impact through pilot studies. This approach has the potential to transform the educational paradigm, prioritizing emotional well-being and fostering a deeper understanding of the life cycle.
Keywords: Primary Education; didactics of death; educational innovation; death education; pedagogy of death